Alpha-Cypermethrin Toxicity in a Labrador Dog: A Case Study - Parmar, JJ; Rao, Neha; Shah, AI; Patel, DM (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
Dogs may be exposed to pesticides used in and around the home. Pesticide toxicity is very common in pets when these drugs are used to control insects and ecto-parasites. Herbicides applied to lawns are also found to be toxic for dogs. Alpha-cypermethrin is an active pyrethroid of many insecticides and effectively controls a wide range of pests in agriculture. Pesticides with alpha-cypermethrin available in the market as a concentrate in suspension or mixed with other insecticides (Luty et al., 1998) comprise the alpha C isomers of cypermethrin which are considered to be two- to three-fold more toxic than cypermethrin and are one of the most effective pyrethroids (Hartnik et al., 2008). This communication reports a case of á-cypermethrin toxicity and its clinical management in a Labrador. Case History and Clinical Observations A four year old Labrador male dog weighing 26 kg was presented under emergency at Veterinary Clinical Complex of the College in Anand with history of ingestion of insecticide containing alpha-cypermethrin. The dog was showing signs of tremor and salivation. The dog was active with mild incoordination of limbs and all the physiological parameters were within normal range.
Keywords: Alpha-cypermethrin; Toxicity; Labrador dog